Prevalence of delayed neurodevelopment in children from Bogotá, Colombia, South America (2007)
Background: Undiagnosed children with neurodevelopment delay disorders (NDD) frequently experience school difficulties, leading to school desertion or academic failure with subsequent familial, social and work-related problems. Methods: In 2004-2005, we conducted a cross-sectional study to determine the prevalence of developmental delay among preschoolers in Bogotá (Colombia); convenience samples in several socioeconomic areas of the city were screened to define the prevalence of NDD. Parents and teachers were interviewed to identify children with possible NDD. Selected children were evaluated with a neurodevelopmental abbreviated scale (EAD-1). Results: We screened 2,043 preschool children aged less than 60 months; 288 suspected cases were examined individually using the EAD-1 scale. One or more abnormal items (alert category) were found in 67 (23.3%) children, for an estimated prevalence of 32.8‰ children less than 5 years of age, including deficits in gross motor function (9.3‰), personal-social interactions (9.8‰), fine motor skills (10.3‰), auditory language delay (18.6‰) and overall delay (10.8‰). Conclusions: There is limited information regarding the prevalence of neurodevelopmental delay in nonindustrialized countries. The prevalence obtained in Bogotá, Colombia, is within the expected range; however, we identified NDD among apparently healthy children from nurseries and kindergartens, who had previously been undiagnosed and untreated. Lack of evaluation of developmental milestones in children in Colombia is a substantial public health problem that will require effective intervention. Copyright © 2007 S. Karger AG.